2009
DOI: 10.1111/j.1365-2958.2009.06948.x
|View full text |Cite
|
Sign up to set email alerts
|

The germinal centre kinase Don3 triggers the dynamic rearrangement of higher‐order septin structures during cytokinesis in Ustilago maydis

Abstract: SummaryThe dimorphic phytopathogenic fungus Ustilago maydis grows in its haploid phase by budding. Cytokinesis and separation of daughter cells are accomplished by the consecutive formation of two distinct septa. Here, we show that both septation events involve the dynamic rearrangement of septin assemblies from hourglass-shaped collars into ringlike structures. Using a chemical genetic approach we demonstrate that the germinal centre kinase Don3 triggers this septin reorganization during secondary septum form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 73 publications
3
45
0
1
Order By: Relevance
“…This scaffolding is thought to provide rigidity to the emerging infection peg. In U. maydis , septins (Alvarez-Tabarés and Pérez-Martín, 2010; Böhmer et al, 2009) as well as Tea4 (this work) and Tea1 (a cell end marker) (Woraratanadharm and Banuett, unpublished) localize to the neck region in the yeast-like cell. It is possible that UmTea1 may have a similar role at the neck as Tea1 in the M. oryzae appressorium pore.…”
Section: Discussionmentioning
confidence: 81%
“…This scaffolding is thought to provide rigidity to the emerging infection peg. In U. maydis , septins (Alvarez-Tabarés and Pérez-Martín, 2010; Böhmer et al, 2009) as well as Tea4 (this work) and Tea1 (a cell end marker) (Woraratanadharm and Banuett, unpublished) localize to the neck region in the yeast-like cell. It is possible that UmTea1 may have a similar role at the neck as Tea1 in the M. oryzae appressorium pore.…”
Section: Discussionmentioning
confidence: 81%
“…Notably, as Clp1-interacting proteins (see Supplemental Table 1 online), we identified Cdc15, a protein required for cytokinesis and nuclear distribution in U. maydis (Bö hmer et al, 2009) and, in addition, the orthologs of BZZ1, Mob1, and CDC36, which were shown to be involved in septum formation, polar growth, and cell cycle control in various fungal species (Hartwell et al, 1970;Reed, 1980;Breter et al, 1983;Luca and Winey, 1998;Luca et al, 2001;Soulard et al, 2002;Weiss et al, 2002;Song et al, 2008;Maerz et al, 2009). A possible role for these proteins during in planta development of U. maydis has not been investigated yet and thus remains speculative.…”
Section: Role Of the Clp1-rbf1 Interaction In Pathogenic Developmentmentioning
confidence: 99%
“…In the dimorphic basidiomycete Ustilago maydis, septins are not essential but are required for normal growth and morphology and localize to the yeast neck and as a band at the growing hyphal tip (1,8). In addition, Sep4 (Cdc10) uniquely formed septin fibers along the cell cortex (1), and septins underwent dynamic rearrangements from hourglass collars into ring structures during septation (7,10). In the rice blast fungus Magnaporthe oryzae, septins form rings that anticipate the site of the appressorium septum (54).…”
mentioning
confidence: 99%